2004
DOI: 10.1068/a36281
|View full text |Cite
|
Sign up to set email alerts
|

New Agendas for Appraisal: Reflections on Theory, Practice, and Research

Abstract: The search for policy rationality is a quest for hope. _ The hope is that individuals may contribute to the pragmatic resolution of the controversies in which they are embroiled, if only they learn how better to conduct their inquiries. '' Scho« n and Rein (1994, page 37) Appraisal: the changing context Assessment of projects, plans, and programmes has been an increasingly important aspect of environmental policy and has latterly been afforded a prominent role in the quest for policy integration and sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
269
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(285 citation statements)
references
References 55 publications
(54 reference statements)
5
269
0
7
Order By: Relevance
“…Taking the first of these assumptions, the evidence that objective information is transferred via IA into policy is somewhat limited (Wood and Jones, 1997;Cashmore et al, 2004;Cashmore et al, 2009;Elling, 2009;Van Buuren and Nooteboom, 2009;Eales and Sheate, 2011). More and more authors argue that decision-making is not rational and that IA, for example, has considerably more roles than simply information provision (see, for example, Lawrence, 2000;Leknes, 2001;Bond, 2003;Bekker et al, 2004;Cashmore, 2004;Owens et al, 2004). Bartlett and Kurian (1999) detail six separate models explaining the role of environmental impact assessment in decision-making, in which the information processing (rational) model is just one end of the spectrum of influence; other models include the symbolic politics model, the political economy model, the organisational politics model, the pluralist politics model and the institutionalist model.…”
Section: Impact Assessment Theory and Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the first of these assumptions, the evidence that objective information is transferred via IA into policy is somewhat limited (Wood and Jones, 1997;Cashmore et al, 2004;Cashmore et al, 2009;Elling, 2009;Van Buuren and Nooteboom, 2009;Eales and Sheate, 2011). More and more authors argue that decision-making is not rational and that IA, for example, has considerably more roles than simply information provision (see, for example, Lawrence, 2000;Leknes, 2001;Bond, 2003;Bekker et al, 2004;Cashmore, 2004;Owens et al, 2004). Bartlett and Kurian (1999) detail six separate models explaining the role of environmental impact assessment in decision-making, in which the information processing (rational) model is just one end of the spectrum of influence; other models include the symbolic politics model, the political economy model, the organisational politics model, the pluralist politics model and the institutionalist model.…”
Section: Impact Assessment Theory and Uncertaintymentioning
confidence: 99%
“…This approach is consistent with the views of Hermans and Knippenberg (2006) who identified that participatory processes are key in a context where stakeholder views on potential outcomes are highly variable amidst high levels of uncertainty, and with the need for great pluralism espoused by Bond et al (2013) when considering assessment of sustainability (participatory deliberation is identified as a suitable method for dealing with ambiguity in Figure 1). Such participatory approaches are also required for the achievement of legitimacy (Walker et al, 2002;Owens et al, 2004) and fit into the participatory discourse framing required for a postnormal science approach to IA.…”
Section: Combining the Parts -Impact Assessment For Building Resilienmentioning
confidence: 99%
“…Tackling the array of contentious issues associated with windfarm developments has often rested on the assumption that ette i fo atio will generate consensus and thereby resolve dispute (Barry, et al, 2008). Despite criticism of this view (Owens, et al, 2004), the generation of such information in planning practice remains inured to linear-rational models of knowledge production that a e assu ed to p o ide the fa ts of a situatio y virtue of their internal merits (Adelle, et al, 2012). This disregards the variety of ways in which the world is interpreted and knowledge claims about reality are produced (Devine-Wright, 2009;Rydin, 2007).…”
Section: A Morementioning
confidence: 99%
“…This perspective privileges quantifiably measurable criteria as alid fo s of k o ledge in impact assessment while concurrently negating alternative forms of knowing not easily crosscomparable, such as the subjective interpretation of experience (Aitken, 2009). As a consequence, much planning activity promotes a ge e al state of easo (Foucault, 1972) set in the ability to underpin governance in an appeal to fa ts conceived in accordance with the methods advanced by technical rationality (Owens, et al, 2004) v . This commitment to seemingly post-politi al o je ti e odes of k o i g e ases the fu da e tal pa ado that the e is o a to fi eut alit eut all (Margolis, 1998, 59), and thereby conceals the bias inherent to favouring one mode of knowledge production over another when it persiste tl fails to esol e the pla i g p o le it seeks to add ess.…”
Section: Con-substantiation Of a Discursive Reality And Authoritativementioning
confidence: 99%
“…Recent efforts at the global level have produced broad sets of procedures to assess sustainable development, currently identified with sets of labels that vary depending on institutional contexts, planning traditions and resource uses (Dalal-Clayton & Sadler 2014). Among these, sustainability 'assessments' or sustainability 'appraisals' are the terms mostly used to identify the procedures to assess the social, economic, and environmental impacts of planning decisions (Owens et al 2004).…”
Section: The Research Background/rationalementioning
confidence: 99%